Peningkatan Pemahaman Remaja Karang Taruna Melalui Sosialisasi Buku Saku Fiqih - Dian Kusuma Wardani; Fitri Umardiyah; Suci Prihatiningtyas; Asiyah Lulu'ul Husna (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2022)
The Fiqh Pocket Book Socialization activity in the context of increasing understanding of fiqh lessons is an activity aimed at youth youth groups in Mojokambang village so that they obtain information, so that awareness arises, accepts and ultimately uses the information to add insight related to fiqh material. The implementation method includes observation, asking permission from partner villages, planning stage, implementation stage (socialization), training and monitoring and evaluation stage. This socialization contains the delivery of material on the importance of learning fiqh for Muslims as a guide to living in accordance with the Qur'an and Hadith as a provision for daily life in facing the challenges of the times. After the socialization, a fiqh discussion seminar was held. The results of the socialization of the fiqh pocket book showed that the participant's response to the material presented was in good category with an average percentage of 89%, the participant's response to the demonstration of fiqh material practice was in good category with an average percentage of 89%. Participants' responses to the media used in the process of learning fiqh material were categorized as good with an average percentage of 80%. The participant's response to the socialization instructor was categorized as good with an average percentage of 79%. So overall the participants gave a positive response to the socialization activity of providing fiqh material as a means to increase insight and knowledge and understanding related to fiqh learning for youth youth in Mojokambang village.